2002
DOI: 10.1097/00003072-200210000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Bilateral Striopallidodentate Calcinosis

Abstract: Bilateral symmetric striopallidodentate calcinosis, also known as Fahr's disease, is characterized by bilateral calcifications of the basal ganglia, thalami, dentate nuclei of the cerebellum, and the white matter of the cerebral hemisphere. Intracranial calcifications are easily visible as high-density areas on computed tomographic images. On magnetic resonance images, the calcifications exhibit different signal intensities. The differences in signal intensity are thought to be related to the stage of the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 7 publications
3
18
0
2
Order By: Relevance
“…Uygur et al [9] found that cerebral blood fl ow was reduced in the frontoparietal cortex (without calcifi cation on CT) in addition to basal ganglionic hypoperfusion. Ogi et al [25] reported that in their patient, perfusion in the basal ganglia and cortex was within the normal limits on calcifi ed regions, but they observed reduced accumulation in both thalami, and concluded that reductions in cerebral perfusion of calcifi ed lesions are not associated with the volume of the calcium deposit. Increased blood fl ow with 99 m Tcethyl cysteinate dimer in both temporal lobes and hypoperfusion in the basal ganglia has also been reported in a patient with schizophrenia-like psychosis [26].…”
Section: Discussionmentioning
confidence: 88%
“…Uygur et al [9] found that cerebral blood fl ow was reduced in the frontoparietal cortex (without calcifi cation on CT) in addition to basal ganglionic hypoperfusion. Ogi et al [25] reported that in their patient, perfusion in the basal ganglia and cortex was within the normal limits on calcifi ed regions, but they observed reduced accumulation in both thalami, and concluded that reductions in cerebral perfusion of calcifi ed lesions are not associated with the volume of the calcium deposit. Increased blood fl ow with 99 m Tcethyl cysteinate dimer in both temporal lobes and hypoperfusion in the basal ganglia has also been reported in a patient with schizophrenia-like psychosis [26].…”
Section: Discussionmentioning
confidence: 88%
“…Confirming this finding, Kanda et al 27 found that the DN and globi pallidi showed significantly higher gadolinium concentrations than the other evaluated brain regions (ie, cerebellar white matter, frontal lobe cortex, and frontal lobe white matter). Similar MR imaging signal-intensity changes in the dentate and/or deep gray nuclei are seen in patients with multiple sclerosis, neurofibromatosis, hypoparathyroidism, manganism, inherited metabolic disorders, and Fahr disease, suggesting that these areas are particularly susceptible to metal deposition 18,19,26,61 ; but these anatomic preferences remain poorly understood. In bone and other tissues, gadolinium deposition can be explained, in part, by the presence of fenestrated capillary systems, in combination with the analogous nature of Gd and Ca.…”
Section: Gadolinium Retention and Tissue Depositionmentioning
confidence: 88%
“…Except by familial cause, with unknown mechanism, genetically determined, all other causes appear to result of calcium deposits by serum abnormalities (with a change in vascular permeability related to local calcium concentration) 14 or of dystrophic calcifications, with physical abnormalities in small vessel, focal circulatory disabilities and metabolic disorders (hypoxia, hypoglycemia, and abnormalities in the acid-base balance or electrolytes) 15 . Reduced blood flow to calcified regions is confirmed in SPECT of the brain with 99m Tc-hexamethhylpropilenamine ( 99m Tc-HMPAO) 16 .…”
Section: Discussionmentioning
confidence: 99%